2015
DOI: 10.1007/s00436-015-4533-9
|View full text |Cite
|
Sign up to set email alerts
|

Destructive effect of gamma irradiation on Echinococcus granulosus metacestodes

Abstract: Current options for treatment of cystic echinococcosis (CE), including chemotherapeutics and surgical approaches, are not satisfactory in certain cases of resistant cysts in vulnerable or inaccessible organs. Therefore, potential means of therapy are needed. The present work evaluated the effect of gamma irradiation on mestacestode causing CE. Metacestode of Echinococcus granulosus were exposed to 15, 30, and 60 Gy irradiation and examined after 24 h for viability, morphologic, and ultrastuctural alterations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Since deactivation of the germinal layer and protoscolices of hydatid cyst is the main goal of therapeutic methods, this study investigated the mortality rate of protoscolices, as well as structural and apoptotic changes in the hydatid cyst wall. It was found that A. noeanum extracts lead to apoptosis in the cystic wall, which is similar to some previous studies (13).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Since deactivation of the germinal layer and protoscolices of hydatid cyst is the main goal of therapeutic methods, this study investigated the mortality rate of protoscolices, as well as structural and apoptotic changes in the hydatid cyst wall. It was found that A. noeanum extracts lead to apoptosis in the cystic wall, which is similar to some previous studies (13).…”
Section: Discussionsupporting
confidence: 91%
“…It is controlled and regulated by some caspases, including caspase-3 (12). Caspase-3 is an endoprotease, which plays a central role in the execution phase of apoptosis (13). Since apoptosis is a process of cellular self-destruction, it provides a convenient way to eliminate parasitic agents, such as Echinococcus protoscolices (14).…”
Section: Introductionmentioning
confidence: 99%
“…Our results further validate this previous finding, as an increase in apoptotic markers in infertile cysts and decreased apoptosis of inflammatory cells was observed following immunization, leading to the destruction of the larval cestode. Recently, Alam-Eldin & Badawy (2015) reported the apoptosis of hydatid metacestodes following exposure to gamma irradiation, using colorimetric and immunohistochemistry assays of Caspase 3 activity. These results suggest the therapeutic potential of gamma irradiation in CE, and our results highlight a similar potential for disease prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, various mechanical methods and chemical agents have been tested in order to prevent the formation of secondary hydatidosis. The antiparasitic ef-fects of direct electric current [1], magnetic field [2], xray [3], UV light [4], gamma irradiation [5], ultrasound [6,7], nanoparticles [8], hypotonic saline [9], silver nitrate [10], vinegar [11] and various herbal extracts or essential oils have been evaluated on protoscoleces to certain extents [12][13][14].…”
Section: Introductionmentioning
confidence: 99%